2020
DOI: 10.1101/2020.07.22.216499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A pan-cancer atlas of somatic mutations in miRNA biogenesis genes

Abstract: It is a well-known and intensively studied phenomenon that the levels of many miRNAs are differentiated in cancer. miRNA biogenesis and functional expression are complex processes orchestrated by many proteins cumulatively called miRNA biogenesis proteins. To characterize cancer somatic mutations in the miRNA biogenesis genes and investigate their potential impact on the levels of miRNAs, we analyzed whole-exome sequencing datasets of over 10,000 cancer/normal sample pairs deposited within the TCGA repository.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 168 publications
(223 reference statements)
0
1
0
Order By: Relevance
“…It is widely confirmed that miRNAs are involved in the progression of various cancers, which include bladder carcinomas, pancreatic cancer, and hepatocellular carcinomas, etc. ( 26 , 27 ). Hammouz RY et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely confirmed that miRNAs are involved in the progression of various cancers, which include bladder carcinomas, pancreatic cancer, and hepatocellular carcinomas, etc. ( 26 , 27 ). Hammouz RY et al.…”
Section: Discussionmentioning
confidence: 99%